Unresectable Chondrosarcomas Treated With Carbon Ion Radiotherapy: Relationship Between Dose-averaged Linear Energy Transfer and Local Recurrence - MATSUMOTO, SHINNOSUKE; LEE, SUNG HYUN; IMAI, REIKO; INANIWA, TAKU; MATSUFUJI, NARUHIRO; FUKAHORI, MAI; KOHNO, RYOSUKE; YONAI, SHUNSUKE; OKONOGI, NORIYUKI; YAMADA, SHIGERU; KANEMATSU, NOBUYUKI (Anticancer research, 2020)
Background/Aim: The local control rate of chondrosarcomas treated with carbon-ion radiotherapy (CIRT) worsens as tumour size increases, possibly because of the intra-tumoural linear energy transfer (LET) distribution. This study aimed to evaluate the relationship between local recurrence and intra-tumoural LET distribution in chondrosarcomas treated with CIRT. Patients and Methods: Thirty patients treated with CIRT for grade 2 chondrosarcoma were included. Dose-averaged LET (LETd) distribution was calculated by the treatment planning system, and the relationship between LETd distribution in the planning tumour volume (PTV) and local control was evaluated. Results: The mean LETd value in PTV was similar between cases with and without recurrence. Recurrence was not observed in cases where the effective minimum LETd value exceeded 40 keV/μm. Conclusion: LETd distribution in PTV is associated with local control in chondrosarcomas and patients treated with ion beams of higher LETd may have an improved local control rate for unresectable chondrosarcomas.